2021
DOI: 10.1051/0004-6361/202038381
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling stellar populations in the Andromeda Galaxy

Abstract: To understand the history and formation mechanisms of galaxies, it is crucial to determine their current multidimensional structure. In this work, we focus on the properties that characterise stellar populations, such as metallicity and [α/Fe] enhancement. We devised a new technique to recover the distribution of these parameters using spatially resolved, line-of-sight averaged data. Our chemodynamical method is based on the made-to-measure framework and results in an N-body model for the abundance distributio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 128 publications
(219 reference statements)
0
8
0
Order By: Relevance
“…Finally, there are tentative hints of a thickened disk in the 3D chemical structure of M31, as inferred from "made-to-measure" chemo-dynamical modeling of integral field spectroscopy of M31 (Gajda et al 2021). The authors find flaring in the overall metallicity, and a tendency toward larger α-enhancement at larger scale heights, which they argue is consistent with thickening due to a major merger as advocated for by Hammer et al (2018), D'Souza & Bell (2018b), and Bhattacharya et al (2019.…”
Section: Other Indicators Of M31's Thickened Diskmentioning
confidence: 72%
“…Finally, there are tentative hints of a thickened disk in the 3D chemical structure of M31, as inferred from "made-to-measure" chemo-dynamical modeling of integral field spectroscopy of M31 (Gajda et al 2021). The authors find flaring in the overall metallicity, and a tendency toward larger α-enhancement at larger scale heights, which they argue is consistent with thickening due to a major merger as advocated for by Hammer et al (2018), D'Souza & Bell (2018b), and Bhattacharya et al (2019.…”
Section: Other Indicators Of M31's Thickened Diskmentioning
confidence: 72%
“…This difference leads to a pronounced horizontal metallicity gradient along the bar's major axis (Wylie et al 2021). The Milky Way (MW) is not unique in this structure, bars with ends that are more metal rich and/or younger than their central regions have been observed in a few other galaxies as well (Seidel et al 2016), including M31 (Gajda et al 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, Saglia et al (2018) found that the stellar metallicity is enhanced along the proposed bar structure. Based on the m2m models in Blaña Díaz et al (2018), Gajda et al (2021) constrained the 3D distribution of metallicity and α-enrichment using observed [Z/H] and [α/Fe] maps (Saglia et al 2018), and an X-shaped metallicity distribution is found in the bulge region. These results imply that M31 is a barred galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Saglia et al (2018) found that the stellar metallicity is enhanced along the proposed bar structure. Based on the m2m models in Blaña Díaz et al (2018), Gajda et al (2021) constrained the 3D distribution of metallicity and α-enrichment using observed [Z/H] and [α/Fe] maps (Saglia et al 2018), and an X-shaped Original content from this work may be used under the terms of the Creative Commons Attribution 4.0 licence. Any further distribution of this work must maintain attribution to the author(s) and the title of the work, journal citation and DOI.…”
Section: Introductionmentioning
confidence: 99%